The art of courtship - Wood, Clement, 1888-1950; Haldeman-Julius, E. (Emanuel), 1888-1951 (Salt Lake City, UT : Project Gutenberg, 2025)
The art of courtship by Clement Wood is a practical guidebook on love and relationships written in the early 20th century. It outlines how and why people woo, frames courtship as both instinct and social practice, and argues that mating should be chosen wisely for lasting happiness. The likely topic is advice on selecting a partner, wooing well, and conducting an engagement with maturity and tact. The book moves from first principles to practice. It traces wooing$1 (Bs biological roots, weighs reasons for and against marriage, and urges both sexes to treat courtship as education in the opposite sex. It advises how to choose a mate$1 (Bbalancing physical attraction, health, age, temperament, intellect, money, and social background$1 (Bwhile warning against (3z(Breform(3y (Bmarriages and purely financial matches. It gives concrete guidance for men on making themselves genuinely attractive, communicating, proposing naturally, and continuing courtship after marriage; and for women, it dismisses gimmicky flirtation (3z(Bcodes,(3y (Bexplains how to judge men, encourages tactful initiative (even proposing), and favors being a frank, fully human partner over being merely (3z(Bnice.(3y (BEngagement etiquette covers rings, public behavior, jealousy, and the fraught question of premarital intimacy, with the engagement treated as a test that may wisely end in marriage$1 (Bor be broken. The closing section samples famous literary courtships and love poetry to inspire better wooing, while underscoring that the art of courtship is ongoing, mutual, and aimed at shared happiness. (This is an automatically generated summary.)s
Release date is 2025-10-04
Tim Miller, BlueDiamondHead and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Courtship